Population dynamics of Pulsatilla patens (L.) Mill. in a new locality in Poland - Ciosek, Marek Tadeusz; Piórek, Katarzyna; Sikorski, Roman; Trębicka, Agata (Biodiversity: Research and Conservation, 2016)
A new locality of Pulsatilla patens (L.) Mill. in the Wyszków-Jegiel Forest District, in the southern part of Puszcza Biała (ATPOL EC79) is described. This locality is situated on an escarpment, at the edge of Peucedano-Pinetum fresh pine forest with elements of Serratulo-Pinetum mixed pine forest and Potentillo albae-Quercetum steppe oak forest. Good light conditions prevail in the place of plant occurrence. Studies carried out in 2008-2015 showed an increasing trend of P. patens population, though, recently, this population seems to be stable. The number of species accompanying the pasque-flower also increased in this time period. It was found based on the analysis of flora directly neighbouring the clumps of the pasque-flower. During 7 years, the number of taxa increased by 31.5% on plot I and by 25% on plot II. In the years 2011-2013, the pasque-flower was represented both by flowering (1-2) and vegetative individuals. Afterwards, the plant was present only in vegetative stage. The number of its leaves varied in time. The highest number of leaves - 14 per individual - was noted in 2014, and the lowest number (1) - in 2012. The reason for a decline in the number of plant clumps in the site Dalekie and, at the same time, the greatest threat was the excavation of sand from the escarpment. In 2012, this escarpment slid down and several clumps of the pasque-flower were destroyed. Forest management and digging up by wild boars were additional factors limiting the population. To preserve the site of P. patens, measures of active protection should be applied.